Accumulation of fertilizer phosphorus in peat soils - Armi Kaila; Hilve Missilä (Scientific Agricultural Society of Finland, 1956)
In the present paper the results of a preliminary study of the accumulation of fertilizer P in peat soils is reported. The material consisted of samples from an old field experiment in Leteensuo Experiment Station and from 12 experiments on newly reclaimed soils in Northern Finland. The primary object of this paper was the consideration of the role of organic P in the accumulation of fertilizer phosphate. Some support was obtained to the assumption that the biological absorption of P performed by microorganisms and plants stores up in organic form a large part of phosphorus applied to peat soils. The fertilizer P accumulated in inorganic forms was generally rather tenaceously fixed. The retention of phosphate against extraction with 0.05 N NaCl solution was high in most of the peat samples.